2022
DOI: 10.3389/fmed.2022.806702
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Perceptions and Intention to Vaccinate Their Children Against COVID-19: Results From a Cross-Sectional National Survey in India

Abstract: BackgroundDespite the success of adult vaccination against COVID-19, providing vaccines to children remains a challenge for policymakers globally. As parents are primary decision-makers for their children, we aimed to assess parents' perceptions and intentions regarding COVID-19 vaccination in India.MethodsA cross-sectional web-based study was designed, parents or caregivers (N = 770) were recruited through snowball sampling using Google form. Cross-tabulation was performed by parents' intention to vaccinate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
2
8
1
Order By: Relevance
“…Parent self-vaccination [ 54 , 64 , 90 , 92 , 101 , 113 , 117 , 119 , 120 , 122 , 125 , 127 , 128 , 132 , 134 , 136 ] or their willingness for self-vaccination [ 65 , 76 , 77 , 86 , 88 , 92 , 98 , 103 , 125 , 127 , 129 ] showed positive association with parents’ willingness to vaccinate their children in almost all studies. Just one study reported that among participants vaccinated against COVID-19, only 29.0% were willing to vaccinate their children [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parent self-vaccination [ 54 , 64 , 90 , 92 , 101 , 113 , 117 , 119 , 120 , 122 , 125 , 127 , 128 , 132 , 134 , 136 ] or their willingness for self-vaccination [ 65 , 76 , 77 , 86 , 88 , 92 , 98 , 103 , 125 , 127 , 129 ] showed positive association with parents’ willingness to vaccinate their children in almost all studies. Just one study reported that among participants vaccinated against COVID-19, only 29.0% were willing to vaccinate their children [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Parents’ education level showed inconsistent results in association with parental willingness for children’s vaccination. Some studies showed positive association of parents’ higher level of education with vaccination willingness [ 38 , 54 , 58 , 59 , 62 , 75 , 76 , 79 , 87 , 89 , 90 , 91 , 93 , 98 , 110 , 126 , 134 ], while others reported negative [ 52 , 74 , 84 , 113 , 116 , 119 , 137 ] or null [ 88 ] association.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This statement supports the findings of the present study in terms of parental education and acceptance of vaccination for their children. In contrast, Padhi et al conducted an online cross-sectional national survey in India to assess parents’ perceptions and intentions to vaccinate their children against COVID-19, reporting greater likelihood of child vaccination among parents having a bachelor’s degree or higher education (OR: 1.98, 95% CI: 1.15–3.51) [ 31 ]. Similarly, Aedh conducted a cross-sectional survey in Najran, Saudi Arabia, reporting that parents with graduate or postgraduate education were more inclined to accept or approve of vaccination against COVID-19 for their children [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“… 14 Similar findings have been reported in the vaccines that target both adults and children, such as influenza and COVID-19 vaccines. 28 , 29 It suggests knowledge and awareness remain crucial for increasing vaccination intent and behavior.…”
Section: Discussionmentioning
confidence: 99%